Re-education trends in Mathematics Teaching (Innovaciones Educativas, 2021)
This scientific editorial sketches out the main criteria and the fundamental principles of the didactic methodologies in Mathematics Teaching gathered throughout my thirty years of experience working in the field as a teacher and a researcher. Developing listening skills as well as adding up to the constant notions of “sense” and “meaning” for the acquisition of mathematical knowledge along with the “sensitivity” variable among other values are vital in the function that determines the learning outcomes.
Keywords: math teaching; learning methods; education; scientific innovation; mathematics